2022
DOI: 10.1175/bams-d-20-0328.1
|View full text |Cite
|
Sign up to set email alerts
|

AERA5-Asia: A Long-Term Asian Precipitation Dataset (0.1°, 1-hourly, 1951–2015, Asia) Anchoring the ERA5-Land under the Total Volume Control by APHRODITE

Abstract: Accurate long-term precipitation information is critical for understanding the mechanisms behind how precipitation couples with Earth’s water fluxes, energy balances, and biogeochemical cycles across space–time scales under the changing climate. This study proposes a novel approach (Daily Total Volume Controlled Merging and Disaggregation Algorithm, DTVCMDA) for generating a new long-term precipitation dataset, AERA5-Asia (0.1°, 1 hourly, 1981–2015, Asia; “AERA5” is a combination of the “A” from APHRODITE and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Importantly, the most outstanding advantage of ERA5 precipitation data is the long time series with high quality confirmed by comprehensive comparisons with satellite‐based precipitation datasets, e.g. IMERG and GSMaP (Ma et al, 2022; Xu et al, 2022). For instance, ERA5 precipitation data show highest performance over subregions of temperate monsoon climate and temperate continental climate over China mainland (Xu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the most outstanding advantage of ERA5 precipitation data is the long time series with high quality confirmed by comprehensive comparisons with satellite‐based precipitation datasets, e.g. IMERG and GSMaP (Ma et al, 2022; Xu et al, 2022). For instance, ERA5 precipitation data show highest performance over subregions of temperate monsoon climate and temperate continental climate over China mainland (Xu et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, ERA5 precipitation data show highest performance over subregions of temperate monsoon climate and temperate continental climate over China mainland (Xu et al, 2022). Moreover, the performance of model‐based precipitation products significantly outperform satellite‐based products over high‐latitude regions in cold seasons (Gao et al, 2020; Ma et al, 2022; Sui et al, 2020; Zhu et al, 2021). Therefore, ERA5 could convincingly stand out among many state‐of‐the‐art global and regional precipitation products obtained through gauge‐based, satellite‐based, and atmospheric retrospective‐analysis models, as well as through the merging of their products (Hersbach et al, 2020; Chen et al, 2008; Harris et al, 2020; Huffman et al, 2007; Huffman et al, 2019; Kobayashi et al, 2015; Ma et al, 2020; Ma et al, 2022, shown in Table 1) in terms of long time series with high quality.…”
Section: Methodsmentioning
confidence: 99%
“…The preceding evaluations were justified using ERA5‐Land as a reference data set in terms of the physical adequacy of water and energy processes. Nevertheless, the adverse influence of wet biases in ERA5 precipitation in China, especially before 2000, on the long‐term trends of SM and ST was considered (Jiao et al., 2021; Z. Q. Ma et al., 2022). Hereafter, we focused on the period 2000–2020 to examine soil temperature‐moisture change regimes.…”
Section: Evaluation Of Reanalysis and Cmip6 Simulation Datamentioning
confidence: 99%
“…Nevertheless, the adverse influence of wet biases in ERA5 precipitation in China, especially before 2000, on the long-term trends of SM and ST was considered (Jiao et al, 2021; Z. Q. Ma et al, 2022). Hereafter, we focused on the period 2000-2020 to examine soil temperature-moisture change regimes.…”
Section: Evaluation Of Reanalysis Datamentioning
confidence: 99%
“…Surface snowfall rate; Microwave; Deep learning; Attention module; Physical constraints 1 Introduction Precipitation is a critical component in water, energy and biogeochemical cycles (Kidd and Huffman, 2011;Ma et al, 2022a;Xu et al, 2022) and snowfall predominates over other types of precipitation in high-latitude regions (Skofronick-Jackson et al, 2015). Today, satellite remote sensing is the primary observational source for gathering data on worldwide rainfall and snowfall since meteorological stations, ocean buoys, and weather radars have limited coverage (Hong et al, 2007;Ma et al, 2022b;Zhu and Ma, 2022).…”
Section: Introductionmentioning
confidence: 99%